Cooperation of pedagogue and pupil and its dependence on pedagogical skill in a condition of modern education system - Aiytzhanova, R.М.; Kitibayeva, А.K. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
The article deals with the problem of interaction of the teacher and the pupil, and its dependence on the pedagogical skill in today's education system. Main characteristics of pedagogical interaction here are mutual understanding, mutual learning, relationships, mutual action, and interference. The article discusses the pedagogical interaction, which can be represented as an individual process (between the tutor and pupil) sociopsychological (interaction in the team) and as an integrated (combining various educational impact in a particular society).
Қазіргі білім беру жүйесіндегі тəрбиеленуші мен педагогтың қарым-қатынасының педагогикалық шеберлікке тəуелділігі
Взаимодействие педагога и воспитанника и его зависимость от педагогического мастерства в условиях современной системы образования
Keywords: educational process; pedagogy; pedagogical interaction; mutual understanding; cooperation; adequate self-esteem; pedagogical skill; methods; teacher's individual style; relationships